Opportunities and Challenges that the use of Universal Design for Learning brings to the enhancement of fourth graders’ speaking skill at a public institution in Rionegro - Antioquia (2023)
ABSTRACT : This action-research aimed to analyze challenges and opportunities that the use of Universal Design for Learning can bring to the enhancement of fourth graders’ speaking skill. It was conducted in a public school in Rionegro, Antioquia with 20 fourth graders. Action strategies included presenting students’ multiple means of representation of the content, engagement and action and expression by means of stations. Data gathering instruments included teacher’s journal, surveys, interviews, and students’ artifacts. Findings referred to opportunities related to Vocabulary and Syntax growth through Multiple Means of Engagement and the Creation of Cooperating Work through Action and Expression. Moreover, findings showed challenges related to Students’ not Progressing in Speaking Skill and the Students’ Ages as an Obstacle for Knowing what to Choose when Options were given.